Solid ion source based on hollow-cylindrical magnetron sputtering discharge - Azarenkov, N.A.; Bizyukov, A.A.; Bizyukov, I.A.; Bobkov, V.V.; Kashaba, A.E.; Krieger, K.; Sereda, K.N.; Tarasov, I.K. (Вопросы атомной науки и техники, 2003)
A new solid ion source is described. The ion source based on hollow-cylindrical magnetron sputtering discharge produces the beam of various solid ions (B, C, Si, Ti, V, Fe, Ni, Ta, W) which are then extracted by an ion optical accelerating system. In this ion source DC discharge is used for generation of the ions of different metals and capacitively coupled RF discharge with a frequency 13.56 MHz is used for generation of the ions of other solid materials.